(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research paper explores the Problems Encountered in Virtual Learning of Grade 12 HUMSS Students at Bestlink College of the Philippines in the New Normal, An Intervention program. The researchers show the problems encountered in the Virtual learning of grade 12 HUMSS students and the recommendations for Intervention programs that can be crafted to address the problems. A qualitative method was implemented to conduct this study, emphasizing objective measurements and the statistical, mathematical, or numerical analysis of data collected through polls, questionnaires, and surveys or by manipulating pre-existing statistical data using computational techniques. The researchers utilized descriptive research design in gathering the needed data. Also, convenience sampling was implemented. The study of Problems Encountered in Virtual Learning helped many students identify some issues they faced while taking Virtual Learning at Bestlink College of the Philippines, especially HUMSS 12 Students, and know how to adjust their studies during distance learning and easily engage to their academic online school work. The Problems Encountered in Virtual Learning gives more benefits to know the disadvantages or issues and how to solve them or to enhance their academic performance between teacher and students during distance learning, especially those involved in teaching and studying in Bestlink College of the Philippines. This Research delivers the Relationship between the Problems Encountered in Virtual Learning in Grade 12 HUMSS students in Bestlink College of the Philippines in the New Normal: An Intervention program.